Making Sustainability Work Best Practices in Managing and Measuring Corporate Social, Environmental, and Economic Impacts - Epstein, Marc J.; Rejc, Adriana (Berrett-Koehler Publishers, 2014)
Now completely updated, Making Sustainability Work is the bible for applying real metrics and best practices to the often-nebulous realm of business sustainability. Mark Epstein and Adriana Rejc Buhovac provide concrete tools for measuring and increasing social and environmental impacts in a manner that businesses can understand and put to real use.
Includes bibliographical references and index. - Print version record
Keywords: Social responsibility of business; Corporations -- Environmental aspects; Industries -- Environmental aspects; Entreprises; Responsabilité sociale; Sociétés; Aspect de l'environnement; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; BUSINESS & ECONOMICS; Econometrics; Corporations; Environmental aspects; Industries; Environmental aspects